Android Educational Game: Introduction to Basic Logic for Children - Nurul Ria Irawan; Nisa Rizqiya Fadhliana; Wahyuni Eka Sari (TEPIAN, 2020)
Introduction to Basic Logic aims to develop children's thinking abilities about numbers and quantities to teach activities that are in accordance with the development of their thinking power. Learning in children requires an educational media game facility, one of which is the Educational Game. This educational type game aims to provoke children's interest in learning the subject matter while playing the game. Mobile games can be an alternative in children's learning. Basically children prefer to play rather than learn. This is natural, because child psychology is playing. Based on these problems an educational game application is made for the introduction of basic logic in Android-based children, so that it can produce alternative learning for children. This educational game is intended for children aged 6-7 years because children aged 6-7 years have begun to understand the concept of numbers and develop sensitivity in solving a problem. And trials are carried out using a questionnaire